518 Bavituximab Effectively Targets Suppressive Myeloid Cells in Patients with Glioblastoma. (1st April 2022) - Choi, Bryan D.; Richardson, Leland G.; Ly, K. Ina; Gerstner, Elizabeth; Curry, William T.
Abstract : INTRODUCTION: Glioblastoma and tumor endothelial cells express phosphatidylserine, an immunosuppressive membrane phospholipid. Bavituximab – a chimeric monoclonal antibody – competitively binds to the β2-glycoprotein 1-phosphatidylserine complex, resulting in anti-tumor immune activation and anti-angiogenesis. Bavituximab may act in the tumor immune microenvironment (TIME) through myeloid cells. METHODS: 33 adults with newly diagnosed glioblastoma were enrolled in this phase II trial (NCT03139916). Bavituximab was given weekly, starting week 1 of Stupp. The primary objective was % overall survival at 12 months. We collected peripheral blood mononuclear cells (PBMCs) at enrollment and at regular intervals thereafter. Tumor tissue was banked and analyzed retrospectively. The nCounter Myeloid Innate Immunity Panel, which includes 770 myeloid-associated genes, was used to profile the myeloid transcriptome in both PBMCs and tumor tissue. Multispectral immunofluorescence was used to characterize the intratumoral immune environment. RESULTS: In the TIME, bavituximab-treated patients saw a reduction in the number of MDSCs. While the pretreatment RNA profile in PBMCs was not associated with outcome, above-median progression-free and overall survival were associated with significantly enriched expression of myeloid-associated genes in pretreatment tumor tissue. CONCLUSION: Bavituximab reduces MDSCs in the glioblastoma microenvironment. Elevated tumor expression of myeloid-associated genes may be a predictive biomarker for response to bavituximab.